Investigation of corrosion effect on the dynamic strength of some structural steels - Branko Pejović; Vladan Mićić; Milorad Tomić (Zaštita Materijala)
By corrosion effect, the surface of the metal becomes so rough that there are reduction in metal strength as a consequence of nicking. It should be added that the continuing effects of corrosion produces deep and sharp notches in the metal. It causes tiny cracks that allow further penetration of corrosion. As results of this activities, the dynamic hardness by simultaneously highly corrosion effect substantially decreases so that it may lead to fatigue failure, as shown in this paper. It is also not possible to establish any qualitative or quantitative legality between dynamic strength and corrosion effects. This hold for the effect of corrosion on unloaded metal element. This must be tested in all chance.